Composition and distribution of benthos at the Istanbul Strait's (Bosporus) outlet area of the Black Sea. - Kiseleva, M I; Mikhailova, T V (PANGAEA, 2017)
Total macrobenthos abundance during RV 'Akademik Kovalevsky' cruise from the target sites of Istanbul Strait (Bosporus outlet), Black Sea 1958-1960. Studies of the benthic fauna in the Bosporus outlet area were made by the Department of Benthos of IBSS, during RV 'Akademik Kovalevsky' cruise (July 1958 and June 1960).A total of 10 benthic stations were sampled at depths of 70–113 m. From these studies three ecological communities could be distinguished, namely Modiolula phaseolina, located to the north-east of the Bosporus outlet, and the ecological communities Sternaspis scutata and Amphiura stepanovi – Terebellides stroemi located to the north-west of the Strait.
Benthos at the Istanbul Strait's (Bosporus) outlet area of the Black Sea during Akademik Kovalevsky cruises in 1958 and 1960
Keywords: DEPTH, water; Kovalevsky1958_benthos; Kovalevsky1960_benthos; Macrozoobenthos; Macrozoobenthos, biomass, wet mass; Number of species; OKEAN; Okean Grab; Peterson grab; PETG; Station label